EFFICIENT SELFISH NODE MANAGEMENT METHOD FOR MANET - dubey, Sandeep; pippal, Ravi kumar Singh (International Journal of Computer Sciences and Engineering, 2025)
In a mobile ad-hoc network, congestion is one among the foremost necessary restrictions that deteriorate the performance of the total network. It’s essential to regulate the info rate utilized by every sender so as to not overload the network, wherever multiple senders vie for link information measure. The Packets at the network is also dropped after they reach the router and can't be forwarded. Several packets area unit dropped whereas excessive quantities of packets make a network bottleneck. The proposed ESNM technique of the research uses the Watchdog method with IRTBDM to cut back the congestion rate at the MANET. The proposed technique provides a higher packet delivery ratio, scale back packet drop ratio and communication overhead over existing methods. These factors are necessary for MANET performance and reliability.